2017
DOI: 10.18393/ejss.284265
|View full text |Cite
|
Sign up to set email alerts
|

Using microbiological leaching method to remove heavy metals from sludge

Abstract: Article Info Received : 13.05.2016 Accepted : 11.07.2016 Microbial leaching is one of the most effective methods to remove heavy metals from sludge. In the conducted researches, the sludge samples were processed with Thiobacillus ferrooxidans and Thiobacillus thiooxidans obtained via cultivation, extraction and purification processes. Heavy metals such as Pb, Cd, Cu and Ni were leached from sludge by Thiobacillus ferrooxidans and Thiobacillus thiooxidans within different substrate concentration and pH value c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Immobilisation of metals by bacteria is an important feature of the activated sludge process [66]. Gu et al [67], have suggested that it may be possible to develop a practical microbiological process to remove metals from water. They evaluated the potential of Zoogloea ramigera cell locs for removal of cadmium and mercury from solution, and found that cells grown in an arginine-glucose medium accumulated considerably less mercury than cells cultivated in trypticase soy broth.…”
Section: Bacteria and Metal Formmentioning
confidence: 99%
“…Immobilisation of metals by bacteria is an important feature of the activated sludge process [66]. Gu et al [67], have suggested that it may be possible to develop a practical microbiological process to remove metals from water. They evaluated the potential of Zoogloea ramigera cell locs for removal of cadmium and mercury from solution, and found that cells grown in an arginine-glucose medium accumulated considerably less mercury than cells cultivated in trypticase soy broth.…”
Section: Bacteria and Metal Formmentioning
confidence: 99%